EDITORIAL - Goh, Pauline Swee Choo; Ratnavadivel, Nagendralingan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Two of the six articles in this issue analyse and discuss the many ways in which teachers and teacher educators are developing new pedagogical practices through new instructional methods and self-evaluation of their practice. The third article provides insights into pre-service teachers’ motivation and effective teaching, while another shows the process by which teachers and teacher educators can cooperate to create a professional learning application for the Chinese language. The remaining two articles critically analysed the on-going debate regarding Moral Education in the Malaysian schools, and the importance of teachers’ attitudes towards co-curricular activities. One article comes from the University of Wollongong, Australia; one comes from an author who is currently a postdoctoral fellow in the University of Cambridge, United Kingdom; and the remaining four are from Malaysia. It is hoped that these articles inspire and support the research, development and reporting of future studies and analysis of aspects of teachers, teaching and teacher educators’ pedagogical practices.